INSTITUTIONAL HORROR: THE MANAGEMENT OF LABOR RELATIONS IN THE ORGANIZATION OF EDUCATION: SCHOOLS AND UNIVERSITIES, A PARADOX IN THE KNOWLEDGE SOCIETY - Marilene Oliveira Nunes (Editora da Universidade de Santa Cruz do Sul, 2011)
The objective of this article is to debate the management of teaching tasks issues in schools and universities. Based on concepts like space and time, the author works to show how the new information technologies, within the globalization changed into continuous flow spaces and non-chronological social time. Despite the fast change in business organizations, in other manner the school and universities still have management models that emphasize traditional concepts of space and time enabling the increase of burocracy that use social control tools through coercion and institucional terrorism to run these organizations.